89. A Collaborative & Novel Antimicrobial Stewardship Initiative– Mandatory Approval of Peripherally Inserted Central Venous Catheters. (31st December 2020) - Patel, Sonal; Vazquez, Jose A; Chase, Aaron; Ebong, Eti
Abstract: Background: Central line-associated bloodstream infections result in thousands of deaths and billions of dollars annually. At the Augusta University Medical Center (AUMC), it was identified that ~50% of peripherally inserted central venous catheters (PICCs) that were placed for intravenous (IV) antibiotic administration were unnecessary. A novel initiative was implemented, which required antimicrobial stewardship/infectious diseases approval for PICC insertions if the indication was for IV antibiotic administration only. The objective of this study was to determine the impact of this initiative. Methods: A retrospective observational study was conducted at the AUMC. All adult patients with a PICC line insertion order for IV antibiotic administration, between December 2017 and May 2019 were included. The vascular access team would forward requests for PICC insertions to the antimicrobial stewardship pharmacist. The pharmacist would approve/disapprove the PICC or recommend an infectious diseases consult. The variables collected were: infection types, infectious diseases consultation, reason for PICC denial and 30-day PICC-related complications. Results: A total of 215 requests for PICC insertion (for IV antibiotics) were placed. Of these, 54% of the requests were denied, while 46% were approved. The reasons for PICC denial included: midline catheter preferred (47%), switched to oral antibiotics (33%), further work-up required (10%), or no antibiotics needed (7%). The types of infections treated were: bone and joint infections (28%), urinary tract infections (13%), intra-abdominal infections (12%), endocarditis/endovascular infections (11%), skin soft tissue infections (9%), pneumonia (7%), catheter-related bloodstream infections (6%), central nervous system infections (6%), bacteremia (4%) and others (4%).The infectious diseases consult team was involved in the care of 79% of the patients. Of those that received a PICC line, only 5% experienced any PICC-related complications. The overall cost savings for PICCs that were denied was ~ $294, 000. Conclusion: Mandatory antimicrobial stewardship/infectious diseases approval for PICC insertion can decrease healthcare cost and reduce the number of unnecessary PICC lines placed. Disclosures: All Authors : No reported disclosures